2010
DOI: 10.1016/j.jctb.2010.04.006
|View full text |Cite
|
Sign up to set email alerts
|

On distance-regular graphs with smallest eigenvalue at least −m

Abstract: A non-complete geometric distance-regular graph is the point graph of a partial linear space in which the set of lines is a set of Delsarte cliques. In this paper, we prove that for a fixed integer m 2, there are only finitely many non-geometric distance-regular graphs with smallest eigenvalue at least −m, diameter at least three and intersection number c 2 2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
20
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 15 publications
2
20
0
Order By: Relevance
“…[5,Lemma 4.1]) Suppose that Γ is a geometric distanceregular graph with valency k ≥ 2, diameter D ≥ 2 and smallest eigenvalue θ D . Then the following hold: [5,Lemma 4.2]) Let Γ be a geometric distance-regular graph with diameter D ≥ 2 and intersection number c 2 ≥ 2. Then τ 2 ≥ ψ 1 holds.…”
Section: Preliminariesmentioning
confidence: 99%
“…[5,Lemma 4.1]) Suppose that Γ is a geometric distanceregular graph with valency k ≥ 2, diameter D ≥ 2 and smallest eigenvalue θ D . Then the following hold: [5,Lemma 4.2]) Let Γ be a geometric distance-regular graph with diameter D ≥ 2 and intersection number c 2 ≥ 2. Then τ 2 ≥ ψ 1 holds.…”
Section: Preliminariesmentioning
confidence: 99%
“…Since the smallest eigenvalue θ D of Γ is bounded below (see Lemma 2.7), it follows by [27] that there are only finitely many non-geometric distance-regular graphs. In particular, they showed that the valency k is bounded above as O(m 2 1 ), where m 1 is the multiplicity of second largest eigenvalue.…”
mentioning
confidence: 99%
“…In particular, Spielman [35] improved the complexity of isomorphism testing of strongly regular graphs, found by Babai [1], using the following result by Neumaier [32]: for a fixed integer θ ≥ 2, there are only finitely many coconnected non-geometric distance-regular graphs with smallest eigenvalue at least −θ and diameter 2. Koolen and Bang [27] generalised this as follows: there are only finitely many coconnected non-geometric distance-regular graphs with smallest eigenvalue at least −θ and with given diameter D ≥ 2 or having the intersection number c 2 ≥ 2 (in fact, the Bannai-Ito conjecture recently proved by Bang et al [5] shows that the latter condition on c 2 is not necessary).…”
mentioning
confidence: 99%
See 2 more Smart Citations